Investigate in the continuum of complexity - Bautista Gil, María Elizabeth
Investigate in the continuum of complexity is a way without borders is to approach the historicity of human thought, where systematization, complementarity, fractality, among others, are common elements of a cosmogonic singularity of scientific events. From a philosophical and epistemological worldview we connote the complex task as a hologram of the theories that somehow the reductionist world decontextualized them from investigative doing. When reflecting on the essential meanings of knowledge, the Jonic legacy should not be underestimated as well as the subsequent ages. It is a long way to go, but this research allows us to decant Complexity in method. “This way forward” breaks the preexisting structures to generate a “persovisión” and worldview of a different style to investigate. From the foregoing, the state of the art of the method is derived from complexity. The body of work is developed through Momentums, consistent with the diversity of actions that the researcher proposes to be investigated, the Momentum I: contains the Epistemic Becoming ... The beginning of a worldview. The Momentum II: Complexity of the problem ... Rapporteur of an enigmatic event. Momentum III: Contextualization of the method ... Rupture of the disciplinary process, among others. The method allows convergence in a new way of doing research, this method seeks solutions to scientific problems in various areas of knowledge, is not a restrictive method for a specific science, it carries a methodological, philosophical, epistemological and gnoseological rigor depending of the subject to investigate.